2015
DOI: 10.2119/molmed.2014.00203
|View full text |Cite
|
Sign up to set email alerts
|

Piwi-Interacting RNAs (piRNAs) Are Dysregulated in Renal Cell Carcinoma and Associated with Tumor Metastasis and Cancer-Specific Survival

Abstract: Piwi-interacting RNAs (piRNAs) are a distinct group of small noncoding RNAs (sncRNAs) that silence transposable genetic elements to protect genome integrity. Because of their limited expression in gonads and sequence diversity, piRNAs remain the most mysterious class of small RNAs. Studies have shown piRNAs are present in somatic cells and dysregulated in gastric, breast and liver cancers. By deep sequencing 24 frozen benign kidney and clear cell renal cell carcinoma (ccRCC) specimens and using the publically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
64
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 24 publications
1
64
0
Order By: Relevance
“…Both piR-932 and PIWIL2 could be potential targets for blocking the metastasis of breast cancer [81]. By deep sequencing 24 frozen benign kidney and clear cell renal cell carcinoma (ccRCC) specimens and using the publically available piRNA database, Li et al [82] found 19 piRNAs were differentially expressed between ccRCC and benign kidney tissue, and 46 piRNAs were associated with metastasis. Among these metastasis-related piRNAs, they found piR-32051, piR-39894 and piR-43607 were derived from the same piRNA cluster at chromosome 17, and were overexpressed in embryonic and neoplastic kidney cell lines compared to benign as well.…”
Section: Introductionmentioning
confidence: 99%
“…Both piR-932 and PIWIL2 could be potential targets for blocking the metastasis of breast cancer [81]. By deep sequencing 24 frozen benign kidney and clear cell renal cell carcinoma (ccRCC) specimens and using the publically available piRNA database, Li et al [82] found 19 piRNAs were differentially expressed between ccRCC and benign kidney tissue, and 46 piRNAs were associated with metastasis. Among these metastasis-related piRNAs, they found piR-32051, piR-39894 and piR-43607 were derived from the same piRNA cluster at chromosome 17, and were overexpressed in embryonic and neoplastic kidney cell lines compared to benign as well.…”
Section: Introductionmentioning
confidence: 99%
“…The generation of mature miR-NAs is a multi-step process that starts in the nucleus and ends in the cytoplasm. 98 PIWI-interacting RNA DQ594040 is one down-regulated piRNA in bladder cancer, and its overexpression can inhibit bladder cancer cell proliferation, colony formation and promote cell apoptosis through up-regulating TNFSF4 protein. II), while other pri-miRNAs are transcribed by RNA Pol.…”
Section: Microrna Smentioning
confidence: 99%
“…97 piR-32051, piR-39894 and piR-43607 were found up-regulated in kidney cancer tissues. 98 PIWI-interacting RNA DQ594040 is one down-regulated piRNA in bladder cancer, and its overexpression can inhibit bladder cancer cell proliferation, colony formation and promote cell apoptosis through up-regulating TNFSF4 protein. 99 As for CRC, piR-651 was found to be up-regulated in tumour tissues, which is associated with metastasis state.…”
Section: Microrna Smentioning
confidence: 99%
“…Recently, our lab has also reported the expression of piRNAs in human brain, and Alzheimer's disease (AD)‐affected brain, epithelial ovarian cancer sub‐types and neuroblastoma . Further, aberrant expression of piRNAs has been documented in cancers such as breast, pancreas, lung, kidney, colorectal, cervical, head, neck, and gastric cancer . However, only a few piRNAs such as piR‐651, piR‐20365, piR‐021285, piR‐932, and piR‐823 have been intensively explored and validated in different cancers to decipher their role in oncogenesis .…”
Section: Introductionmentioning
confidence: 99%
“…11 Further, aberrant expression of piRNAs has been documented in cancers such as breast, pancreas, lung, kidney, colorectal, cervical, head, neck, and gastric cancer. [24][25][26][27][28][29][30] However, only a few piRNAs such as piR-651, piR-20365, piR-021285, piR-932, and piR-823 have been intensively explored and validated in different cancers to decipher their role in oncogenesis. 8,[31][32][33][34] Cheng et al reported that the expression of piR-823 in gastric cancer tissues was significantly lower compared to non-cancerous tissues and its increased expression inhibited growth of gastric cancer cells.…”
mentioning
confidence: 99%